Swimbladder properties of Cyclothone spp. in the northeast Atlantic Ocean and the Western Mediterranean Sea - Sarmiento Lezcano, Airam Nauzet; Olivar Buera, Pilar; Caballero Cansino, María José; Couret Huertas, María; Hernández León, Santiago Manuel; Castellón Masajes,Arturo; Peña Sáenz,María Angeles (Frontiers in Marine Science, 2023)
Non-migratory bristlemouth fishes (Cyclothone spp.) are the most abundant vertebrates on Earth and play an important role in the biological carbon pump by remineralizing organic carbon in deep ecosystems. Acoustic data and net sampling are often used in combination to estimate fish and zooplankton biomass, but this procedure may be subject to several sources of error when applied to mesopelagic species. For instance, the allocation of echoes to species has often been biased by not considering Cyclothone spp. due to the use of nets targeting larger fish. Furthermore, the acoustic properties of the target organisms must be well understood to convert acoustic density into numerical density. The characteristics of a fish’s swimbladder are the most relevant features necessary to assess its acoustic properties. This study provides information on the swimbladder properties of six Cyclothone species inhabiting the meso- and bathypelagic layers in the North Atlantic Ocean and Mediterranean Sea, including swimbladder location within the body, fat tissue content, morphology, morphometry (only available for C. braueri and C. pseudopallida), and fish body-mass density (only available for C. braueri, C. pseudopallida, C. pallida, and C. pygmaea). The studied species showed a functional physoclistous swimbladder, with well-developed gas glands and rete mirabile and numerous capillaries in the case of the shallower species C. braueri and C. pseudopallida (mainly distributed from 400 to 600 m depth), and a fat-invested swimbladder in species with deeper vertical distribution (C. livida, C. microdon, C. pallida, and C. pygmaea). The fat content in the swimbladder (C. pallida and C. microdon) increased with depth and latitude, reducing the space in the swimbladder that could contain gas. Changes in swimbladder size and volume during growth were analyzed for shallower species, where swimbladder volume and equivalent radius followed negative allometric growth in relation to body length. Finally, values of body-mass density (ρ) and ...